Chasing the Fish Oil—Do Bunker Vessels Hold the Key to Fisheries Crime Networks? - Ford, Jessica H.; Bergseth, Brock; Wilcox, Chris (Frontiers in Marine Science, 2018)
Illegal, Unreported and Unregulated (IUU) fishing is recognised as a major threat to the health of the world’s oceans. In addition, the discourse around IUU is recognizing and recommending that IUU be viewed through the lens of transnational crime. Reducing IUU fishing therefore requires a detailed understanding of how fishing fleets function and interact transnationally. However, this is difficult to determine because IUU fishing is by nature a clandestine activity, and often occurs in contexts that, by intention, make monitoring very difficult. Disentangling fleet activities therefore necessitates identifying and understanding how key players or actors function to support or guide IUU activities. In this regard, recent efforts have focused on identifying transhipment activities by finding and following refrigerated cargo (reefer) vessels. We suggest that bunker (fuel) vessels, may provide one solution to understanding and unravelling these IUU networks for two main reasons: they are fewer in number, are known to provide additional support to fishing vessels beyond refuelling. In this respect, bunker vessels are also used to resupply provisions, and crew, thereby facilitating human trafficking and slavery, which is demonstrably rife in certain components of the commercial fishing realm (e.g., long distance or high seas fleets). Here, we illustrate how social network analysis could be used as a methodological lens to expose previously clandestine IUU fishing fleet dynamics. Specifically, we highlight the connectedness of a tanker vessel, and several fishing and reefer vessels, in an area in the Southern Indian Ocean that has high levels of fishing and general shipping.